Synergistic effects of basalt fiber and volcanic pumice powder in high-strength geopolymer concrete - Mohamed Abdellatief; Hassan Hamouda; Martin T. Palou; Taher A. Tawfik (Scientific Reports)
Abstract This paper explores the synergistic effects of basalt fiber (BF) and volcanic pumice powder (VPP) on the physico-mechanical, thermal characteristics, efflorescence, and microstructure of high-strength geopolymer concrete (HSGC). HSGC mixtures were developed by partially replacing ground granulated blast furnace slag with 0–40% VPP while incorporating BF in the range of 0–1.5%. The experimental findings demonstrate that increasing BF content from 0.75 to 1.5% significantly enhances compressive, flexural, and splitting tensile strengths, with compressive strength increasing by up to 14.51% at 28 days and flexural and splitting strengths improving by 13.17% and 14.46%, respectively. Conversely, higher VPP content generally reduces compressive strength, with a 40% replacement leading to a 23% decline at 7 days. Moreover, while increased BF levels improved the microstructure and thermal stability, higher volumes of VPP were found to deteriorate the microstructure, thereby accelerating the efflorescence process. Particularly, the HSGC sample containing 10% VPP significantly reduced both the crystal area and thickness compared to other mixtures. A multi-objective optimization approach revealed that higher BF content improved HSGC properties, whereas higher VPP levels diminished performance. The optimal HSGC formulation achieved a compressive strength of 59.25 MPa, a splitting strength of 7.51 MPa, a flexural strength of 8.64 MPa, and a dry density of 2012 kg/m3, with 0.69% BF and 17.79% VPP. Macroscopic and thermal analyses demonstrated that the optimal HSGC sample exhibited a more compact microstructure, demonstrating the effectiveness of response surface methodology in identifying the ideal mixture parameters for HSGC design.